Density of Compatible Ligands on the Surface of Food Particles Modulates Sorting Efficiency in the Blue Mussel Mytilus edulis - Pales Espinosa, Emmanuelle; Eckstein, Margot; Allam, Bassem (Frontiers in Marine Science, 2022)
The adhesion between food particles and mucus is a fundamental process in particle sorting in suspension-feeding bivalves that requires specific recognition. Interactions between carbohydrate-binding proteins (lectins) expressed on the feeding organs and carbohydrates present on microbial cell surface can provide this specificity. Microalga cell surface carbohydrates (MCSC) represent unique patterns that can be considered as species-specific fingerprints. In this study, sorting efficiencies in blue mussels Mytilus edulis fed with microalgae having modified MCSC and engineered microspheres coated with target carbohydrates was measured. The nature and quantities of surface carbohydrates required to trigger sorting in mussels was evaluated and the relationship between ligand quantities and sorting efficiency (SE) was determined. Mussels fed with Chlamydomonas which MCSC were blocked with ConA or PEA lectins (affinity to mannose and glucose) led to a significant decrease of the sorting efficiencies, not observed when the lectin UEA (affinity to fucose) was used. The ability of commercial lectins to inhibit sorting was not linear and a threshold was noted between 30 and 45 ug lectins per million algae cells. Further, mussels were fed with microspheres coated with neoglycoproteins. Results showed that glucose-BSA, but not fucose-BSA, has an effect on particle sorting in mussels, and 1.08 x 109 molecules of glucose per microspheres, corresponding to a density of 6.99 x 106 molecules of glucose per µm2, triggers particle selection. These findings support that selection of food particles by mussels rely on the strength of the bond between suspended particle and the mucosal layer that mediate sorting, and that these bonds depend on the quantity of compatible ligands on each particle.